STUDY OF SULFIDE MINERAL OXIDATION RATES IN OVERBURDEN OF COAL STRATA - Setia Wahyudi, Herry
Inclining of rate of the acid mine drainage (AMD) is mostly influenced by coal mining activities because of overburden excavation which contain of oxidized sulfide minerals. In this term, the mining company had to study carefully for reaching out the minerals contents as well based on government regulation that related to environmental issues. The study should be figured out from geochemical approach as well as the AMD rate (known as pyrite).